(untitled) (Comprehensive Journal of Science, 2025)
The meaning of words, when considered individually, is determined through dictionaries. However, despite their comprehensiveness and accuracy in providing most meanings, they are still limited in delivering the complete meanings of a word in all its different contexts and according to the speech situations in which the words are used. They cannot provide us with the final indication that should be understood from them. Therefore, the meaning of words is determined only through their relationship and adjacency to others. Each word has a primary lexical meaning generally defined by the dictionary, and undoubtedly its value increases and the intended meaning is specified through the context, which plays its role in determining the precise meaning